Information Support of Investor Behavior in the Stock Market - S. GERASYMENKO (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
The Ukrainian stock market being at the initial phase of formation, its low performance results in the inattractiveness of the Ukrainian economy for domestic and foreign investment. With poor awareness of theoretical principles underlying stock market operations, participants of the domestic stock market require advanced professional skills and competencies, especially ones related with information support.  In focus of the article are applications of statistical methods in decision-making by investors in the stock market. A detailed description of the stock market performance in Ukraine is given. The barriers on the way to obtaining comprehensive information on partners, subject of transaction and stock market conjuncture in Ukraine are determined. A scheme of statistical support for stock market analysis and forecasting is proposed; the objectives of statistical analysis of the stock market for various investor categories are outlined; the phases of assessment of the issue’s investment attractiveness are determined, with providing its algorithm. The types and causes of risks immanent in the stock market events are summed up.        The proposed approach allows for creating and using statistical information to justify the choice of market segment and a particular issuer whose securities, once purchased, should contribute to the investor’s goal. Statistical assessment of phenomena and processes in the stock market and its modeling and forecasting on the appropriate statistical basis will increase the efficiency of investment, which should have a positive impact on the economic development.